Analisis Teori 4 Kaidah Atomic Habits Karya James Clear Sebagai Alternatif Model Penanaman Pendidikan Karakter di Tingkat SMA - Galang Dwi Aprilian; Fathi Hidayah; Jon Iskandar Bahari (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study examines the persistent challenge of inconsistent character development in high school students, which leads to a